Hedgehog-activated fat4 and PCP pathways mediate mesenchymal cell clustering and villus formation in gut development - Rao-Bhatia,A; Zhu,M; Yin,W-C; Coquenlorge,S; Zhang,X; Woo,J; Sun,Y; Dean,CH; Liu,A; Hui,C-C; Shivdasani,RA; McNeill,H; et al. (Developmental Cell, 2020)
During development, intestinal epithelia undergo dramatic morphogenesis mediated by mesenchymal signaling to form villi, which are required for efficient nutrient absorption and host defense. Although both smooth-muscle-induced physical forces and mesenchymal cell clustering beneath emerging villi are implicated in epithelial folding, the underlying cellular mechanisms are unclear. Hedgehog (Hh) signaling can mediate both processes. We therefore analyzed its direct targetome and revealed GLI2 transcriptional activation of atypical cadherin and planar cell polarity (PCP) genes. By examining Fat4 and Dchs1 knockout mice, we demonstrate their critical roles in villus formation. Analyses of PCP-mutant mice and genetic interaction studies show that the Fat4-Dchs1 axis acts in parallel to the core-Vangl2 PCP axis to control mesenchymal cell clustering. Moreover, live light-sheet fluorescence microscopy and cultured PDGFRα+ cells reveal a requirement for PCP in their oriented cell migration guided by WNT5A. Therefore, mesenchymal PCP induced by Hh signaling drives cell clustering and subsequent epithelial remodeling.